Real earning management and firm performance of firms listing on Hanoi stock exchange in the context of promoting sustainability disclosure - Nguyen, La Soa; Thi, Phuong Anh Tran; Thi, Phuong Anh, Nguyen; Hoang, Viet Ha; Thi, Van Anh Nguyen (Asian Economic and Financial Review, 2025)
This study investigates the impact of earnings management through real transactions (REM) on corporate financial performance (FP), mediated by sustainability disclosure. Using a sample of 192 companies listed on the Hanoi Stock Exchange (HNX) from 2019 to 2023, the authors analyze the effect of REM on FP, measured by Return on Assets (ROA) and Tobin’s Q, representing accounting-based and market-based performance, respectively. The study also examines the mediating role of environmental, social, and governance (ESG) disclosure in this relationship, given its growing importance. Control variables include company size (SIZE), financial strength (Z-SCORE), growth (GROWTH), and audit quality (AUDIT). Secondary data from financial statements and primary ESG scores based on the Global Reporting Initiative (GRI) Standard are analyzed using STATA. Findings reveal that REM negatively impacts FP, with ESG disclosure acting as a significant mediator. The results suggest that firms engaging in REM undermine their financial performance, particularly when sustainability transparency is considered. Consequently, the study emphasizes the need for businesses to prioritize long-term development, strengthen ESG practices, and curb REM activities to sustain financial health and stakeholder trust. Practical implications highlight the importance of integrating ESG standards into corporate strategy to mitigate the adverse effects of short-term earnings manipulation.